Resonance production at SPS energies: CERES and NA49 - Busch, Oliver (Resonance Workshop at UT Austin, 2012)
We present results on resonance production by the NA49 and CERES collaborations. The measurement of the differential yields and spectral distributions of the K*(892), Δ(1232), ρ, ϕ and Λ(1520) resonances from their leptonic and hadronic decay channels at different C.M.S. energies and for various colliding systems allows us to study in-medium modifications of the resonance mass, width and yield and constrains the properties of the hadronic phase. For K*(892)0, a strong system size dependence of the yield relative to kaon production is found. The production of the Δ(1232) resonance is consistent with thermal model expectations. ϕ meson spectra and yields reconstructed in the leptonic and hadronic decay channels are in agreement. Low-mass dilepton spectra indicate significant regeneration of the ρ meson and a strong modification of the ρ spectral function.